Effects of triglycerol monostearate on physical properties of recombined dairy cream. (April 2020) - Li, Meiling; Li, Yan; Wang, Ruican; Wang, Yunna; Li, Yang; Zhang, Liebing
Abstract: Up to 0.9% (w/w) triglycerol monostearate (TGMS) was added as a stabiliser to recombined dairy cream (RDC), containing 36% anhydrous milk fat (AMF). The physical properties, such as droplet size, surface protein mass, ζ-potential, rheological characteristics, creaming stability, and whipping qualities, were compared based on the TGMS concentration. TGMS addition significantly improved the stability and whipping properties of RDC compared with cream stabilised with milk protein alone. Higher TGMS level substantially increased the viscosity and ζ-potential, narrowed droplet size distribution, and decreased average droplet size. Increasing the TGMS concentration during the whipping process resulted in a shorter whipping time, increased overrun, reduced serum loss, and softer cream texture. Furthermore, the adsorbed protein mass on the interface decreased from 1.14 ± 0.01% to 0.60 ± 0.04% in the presence of TGMS concentrations of 0.5% and higher, indicating the effective displacement of almost half of these proteins.